Antibacterial and hemostatic composite gauze of N, O-carboxymethyl chitosan/oxidized regenerated cellulose. Issue 97 (4th October 2016) - Cheng, Feng; He, Jinmei; Yan, Tingsheng; Liu, Changyu; Wei, Xinjing; Li, Jiwei; Huang, Yudong
Abstract : Viscose gauze was oxidized with NO2 /CCl4 to prepare Oxidized Regenerated Cellulose (ORC). Abstract : Viscose gauze was oxidized with NO2 /CCl4 to prepare Oxidized Regenerated Cellulose (ORC). Then, ORC was modified by the water-soluble chitosan derivative N, O -carboxymethyl chitosan ( N, O -CS). This was synthesized via the reaction of chitosan with chloroacetic acid as the etherification agent in the presence of alkaline. It was prepared by introducing carboxymethyl groups onto the N and O -positions of the chitosan and the substituting degree (DS) of N, O -CS reached 1.68. Composite gauzes with a 2–8 w/v% N, O -CS content were prepared in water solution. Composite gauzes could still maintain their original morphological form and have excellent water-solubility. The formation of an amide bond between the carboxyl group of ORC and the amino group of N, O -CS was confirmed by FT-IR and elemental analysis. To study the influence of carboxymethyl groups on chitosan, the thermal stability and crystallinity of N, O -CS were tested by XRD and TG. Based on SEM images, N, O -CS tended to be adsorbed on the surface of ORC fiber. The antibacterial performance of N, O -CS/ORC gauzes was enhanced with the increases of N, O -CS content. Moreover, N, O -CS/ORC gauzes showed excellent bactericidal activity against both Gram-positive and Gram-negative bacteria. The hemostatic evaluation indicated that the N, O -CS/ORC composite gauzes in rabbit livers had dramatic hemostatic efficacy. The prepared composite gauzes were anticipated to be an optimal material in preventing post-operative adhesion.